Curcumin modulates neurogliogenesis and purinergic receptor expression in neural precursor cells infected with Toxoplasma gondii - Bissacotti B.F. (2023)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.Toxoplasma gondii is an obligate intracellular parasite that causes toxoplasmosis, and its congenital transmission is of paramount concern. During embryonic development, infection with the parasite causes irreversible damage to the still-forming fetus’s central nervous system (CNS). In the pathogenesis of neurotoxoplasmosis, purinergic receptors prejudice neuroprotection, neuroinflammation, and activation of microbicide mechanisms against the parasitic vacuole. This study used curcumin as a treatment for neural precursor cells (NPCs) infected with T. gondii. The congenital toxoplasmosis induction consisted of maternal infection with the VEG strain, and NPCs were obtained from the telencephalon of mouse embryos. Curcumin at increasing concentrations was administered in vitro to analyze NPC metabolic activity, cell number, and size, as well as neurogliogenesis, proving to be effective in recovering the size of infected NPCs. Curcumin partially re-established impaired neurogenesis. Purinergic A1, A2A, and P2X7 receptors may be related to neuroprotection, neuroinflammatory control, and activation of mechanisms for inducing the parasite’s death. ERK 1/2 was highly expressed in infected cells, while its expression rates decreased after the addition of the treatment, highlighting the possible anti-inflammatory action of curcumin. These findings suggest that curcumin treats neurological perturbations induced by toxoplasmosis.